Extracellular Citrate Fuels Cancer Cell Metabolism and Growth - Haferkamp, Sebastian; Drexler, Konstantin; Federlin, Marianne; Schlitt, Hans J.; Berneburg, Mark; Adamski, Jerzy; Gaumann, Andreas; Geissler, Edward K.; Ganapathy, Vadivel; Parkinson, E. Kenneth; Mycielska, Maria E. (Frontiers in Cell and Developmental Biology, 2020)
Cancer cells need excess energy and essential nutrients/metabolites not only to divide and proliferate but also to migrate and invade distant organs for metastasis. Fatty acid and cholesterol synthesis, considered a hallmark of cancer for anabolism and membrane biogenesis, requires citrate. We review here potential pathways in which citrate is synthesised and/or supplied to cancer cells and the impact of extracellular citrate on cancer cell metabolism and growth. Cancer cells employ different mechanisms to support mitochondrial activity and citrate synthesis when some of the necessary substrates are missing in the extracellular space. We also discuss the different transport mechanisms available for the entry of extracellular citrate into cancer cells and how citrate as a master metabolite enhances ATP production and fuels anabolic pathways. The available literature suggests that cancer cells show an increased metabolic flexibility with which they tackle changing environmental conditions, a phenomenon crucial for cancer cell proliferation and metastasis.